Functional distribution of Ca2+-coupled P2 purinergic receptors among adrenergic and noradrenergic bovine adrenal chromaffin cells - Tomé, Ângelo R. (2007)
Background Adrenal chromaffin cells mediate acute responses to stress through the release of epinephrine. Chromaffin cell function is regulated by several receptors, present both in adrenergic (AD) and noradrenergic (NA) cells. Extracellular ATP exerts excitatory and inhibitory actions on chromaffin cells via ionotropic (P2X) and metabotropic (P2Y) receptors. We have taken advantage of the actions of the purinergic agonists ATP and UTP on cytosolic free Ca2+ concentration ([Ca2+]i) to determine whether P2X and P2Y receptors might be asymmetrically distributed among AD and NA chromaffin cells. Results The [Ca2+]i and the [Na+]i were recorded from immunolabeled bovine chromaffin cells by single-cell fluorescence imaging. Among the ATP-sensitive cells ~40% did not yield [Ca2+]i responses to ATP in the absence of extracellular Ca2+ (Ca2+o), indicating that they expressed P2X receptors and did not express Ca2+- mobilizing P2Y receptors; the remainder expressed Ca2+-mobilizing P2Y receptors. Relative to AD-cells approximately twice as many NA-cells expressed P2X receptors while not expressing Ca2+- mobilizing P2Y receptors, as indicated by the proportion of cells lacking [Ca2+]i responses and exhibiting [Na+]i responses to ATP in the absence and presence of Ca2+o, respectively. The density of P2X receptors in NA-cells appeared to be 30–50% larger, as suggested by comparing the average size of the [Na+]i and [Ca2+]i responses to ATP. Conversely, approximately twice as many AD-cells expressed Ca2+-mobilizing P2Y receptors, and they appeared to exhibit a higher (~20%) receptor density. UTP raised the [Ca2+]i in a fraction of the cells and did not raise the [Na+]i in any of the cells tested, confirming its specificity as a P2Y agonist. The cell density of UTP-sensitive P2Y receptors did not appear to vary among AD- and NA-cells. Conclusion Although neither of the major purinoceptor types can be ascribed to a particular cell phenotype, P2X and Ca2+-mobilizing P2Y receptors are preferentially located to noradrenergic and adrenergic chromaffin cells, respectively. ATP might, in addition to an UTP-sensitive P2Y receptor, activate an UTP-insensitive P2Y receptor subtype. A model for a short-loop feedback interaction is presented whereby locally released ATP acts upon P2Y receptors in adrenergic cells, inhibiting Ca2+ influx and contributing to terminate evoked epinephrine secretion